Komodifikasi Pakaian Adat Kabhantapi dalam Tradisi Pernikahan di Kecamatan Tikep Kabupaten Muna Barat - Titin Hartini; Rahmat Sewa Suraya; La Ode Marhini (LISANI: Jurnal Kelisanan, Sastra, dan Budaya, 2023)
This study aims to describe the form of using Kabhantapi in the wedding tradition in Tikep District, West Muna Regency and to describe the commodification of Kabhantapi in the wedding tradition of Tikep District, West Muna Regency. The theory used in this research is the theory of cultural change using descriptive qualitative research methods. The results show that 1) the use of Kabhantapi in the wedding tradition consists of three layers, the first layer is called hamamu, the second layer is bheta wuna, and the third layer is salenda. 2) the use of Kabhantapi is commodified in terms of model and in terms of the use of sarongs. The commodification of Kabhantapi is also a source of community income